QARAQALPAQ TILINDE AYÍRÍM MUZÍKALÍQ ÁSBAP ATAMALARÍNÍŃ LEKSIKA-SEMANTIKALÍQ ÓZGESHELIKLERI - Qarasaev, A. (ILIM hám JÁMIYET, 2022)
This article explores the lexical and semantic differences of various terms about musical instruments in the Karakalpak language. They are divided into certain groups and are revealed semantic differences. It mentions the use of stringed musical instruments such as kobyz, dutar, girjek and dombra. It’s provided information on the origin of some terms of musical instruments. Also included are terms for parts of old musical instruments. Comprehensive study of musical terms contributes to the development of Karakalpak terminology.